Facile Preparation of 1T/2H‐Mo(S1‐xSex)2 Nanoparticles for Boosting Hydrogen Evolution Reaction. Issue 8 (26th March 2019) - Lin, Zhiping; Lin, Bo; Wang, Zongpeng; Chen, Shougang; Wang, Chengwei; Dong, Mengyao; Gao, Qiang; Shao, Qian; Ding, Tao; Liu, Hu; Wu, Shide; Guo, Zhanhu
Abstract: 2D transition metal dichalcogenides with a formula MoX2 (X=S or Se) have been explored as promising earth‐abundant catalysts for hydrogen evolution reaction (HER), especially those with 1T phases. Theoretical calculations and experiments have indicated that optimal catalytic performance can be achieved by regulating the atomic ratio of S and Se in Mo(S1‐ x Se x )2 . However, the preparation of 1T phase Mo(S1‐ x Se x )2 is challenging because of the differences of S and Se elements. Here, we propose a facile and effective hydrothermal method for the production of 1T/2H Mo(S1‐ x Se x )2, with which products with various x values are prepared. The as‐prepared Mo(S1‐ x Se x )2 samples give a low Tafel slope of 42.8 mV dec −1 ( x =0.25), and an overpotential of 161 mV ( x =0.5), which are state‐of‐the‐art among the tremendous MoX2 works. The excellent electrocatalytic performance is derived from the coexistence of S and Se atoms which reduces the reaction potential energy, and the presence of the 1T phase which improves the conductivity. Additionally, the ratio of 1T phase to 2H phase of Mo(S1‐ x Se x )2 is found controllable over reaction temperature. Abstract : A global collaboration : We first proposed one‐step hydrothermal method to prepare 1T/2H−Mo(S1‐ x Se x )2, and Mo(S0.75 Se0.25 )2 gives a low Tafel slope of 42.8 mV dec −1 .